SISTEM MONITOR BUDI DAYA SARANG BURUNG WALET BERBASIS ESP32-CAM DILENGKAPI APLIKASI TELEGRAM - Dani Maulana; I Gusti Agung Putu Raka Agung; I Putu Elba Duta Nugraha (Program Studi Teknik Elektro UNUD, 2022)
Swiftlet nest farming is one of the businesses found in Indonesia due to its bigeconomic value. Nest quality at the time when harvest is able to impact the selling price ofswiftlet nest. Farmers usually monitor the swiftlet nest by checking the nest directly in thebuilding, this matters because the swiftlet is shocked. Monitoring is needed for checking thephysical condition of the swiftlet nest. This research will make a prototype hopefully useful toswiftlet nest farmers as a reference to increase nest quality with high economic value. Theresearch has been done on software and hardware design by ESP32-CAM and Arduino IDEsoftware for making the source code. The result from research of a monitoring system onswiftlet nest farming based ESP32-CAM equipped with telegram is able to send commandsmenu to telegram, capturing photo of swiftlet nest, turning on flash and turning off flash onESP32-CAM. The research has been realized successfully as design.